The Service Compensation of National Health Insurance and The Performance of Health Workers - Daniyah, Robiatud; Marchianti, Ancah Caesarina Novi; Viphindrartin, Sebastiana (Health Notions, 2018)
Public health center is primary facilities service which owned by a government. Complains which occurs in society, such as the procedures of National Healthcare Insurance (JKN) that more complicated, start from gradual administration, participants data validation that need much time was though more convoluted and customer services that given by health workers wasnât done in a good standard and unsatisfied, so the patients will not willingly come back in public health center. The result data of performance measurement of public health in 2016 showed was less; under 80%. The aim of this research was to analyze the influence of service compensation of JKN on health worker performance. This research was quantitative with observational analytical approach. Sample of this research were 36 health workers in Kalisat, 32 health workers in Jelbuk, and 32 health workers in Andongsari public health center who taken by simple random sampling. Partial Least Square (PLS) using smart PLS software was used as method to analyze data. Based on the test result there was positive influence of service compensation on performance, T statistic was 7.730 (t statistic > t table significant 1.96) it meant that the higher an expected performance, it will produce optimal health care service for society. Health workers can do some efforts in improving performance, so it can improve service compensation that given for society. Government need to review about performance assessment that is currently used, such as SKP so the performance assessments were more effective in evaluating.